Sexually Transmissible Infections in Clinical Practice A problem-based approach - McMillan, Alexander; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Sexually Transmissible Infections in Clinical Practice is a problem-based handbook for dealing with commonly-encountered scenarios at the Sexual Health Clinic or the Family Physician$1 (Bs office. Including 35 cases, it covers a rich variety of complaints, and equips the reader with the confidence to deal with cases in STIs. The presentation of each case is followed by questions designed to prompt the reader towards a refined differential diagnosis. Explanatory text instructs the reader on the relevant history to attain from the patient, the interpretation of laboratory results and the treatment of the complaint. Augmented by tables and illustrations, this book is suitable both for teaching and for quick reference in the clinic. For those who require more in-depth information on the epidemiology, pathogenesis and details of the micro-organisms involved in the infections, references to textbooks and review articles are provided. This book will prove very useful for students of medicine and dermatovenereology. It will also provide a helpful refresher for family physicians and practice nurses who wish to become more involved in sexual health, and for family planning doctors and nurses who are being increasingly called upon to manage STIs. Alexander McMillan, MD, MRCP, FRCP, has 27 years$1 (Bexperience as Consultant Physician in Genitourinary Medicine at the Lothian University Hospitals NHS Trust. An experienced teacher as well as practitioner, he is a Senior Lecturer in Genitourinary Medicine at the University of Edinburgh.s
SECTION - A -- A Man Requesting a Sexual Health Screen -- A Woman Requesting a Sexual Health Screen -- A Female Sex Industry Worker Requesting a Sexual Health Screen -- A Gay Man Requesting a Sexual Health Screen -- A Man with Urethral Discharge (1) -- A Female Contact of a Man with Presumed Non-gonococcal Urethritis -- Urethral Discharge (2) -- A Female Contact of a Man with Gonorrhoea -- A Woman wih Increased Vaginal Discharge (1) -- Vaginal Discharge (2) -- Pruritus Vulvae -- A Man with a Red, Itchy Penis -- A Man with Scrotal Pain -- A Young Woman with Abdominal Pain (1) -- A Young Woman with Genital Lumps -- A Young Woman with Genital Ulceration -- A Woman with Recurrent Genital Herpes -- A Gay Man with a Genital Ulcer -- An African Man with a Skin Rash -- A Gay Man with Anal Discharge -- A Gay Man with a Rash, Lymphadenopathy, and Fever -- SECTION - B -- A Young Man with Persistent Urethral Symptoms -- A Man with Severe Dysuria -- A Young Man with a Painful Swollen Knee Joint -- A Woman with Recurrent Pruritus Vulvae -- A Woman with Pruritus Vulvae (2) -- A Young Woman with Abdominal Pain -- Gonococcal and Chlamydial Infections in a Pregnant Woman -- A Pregnant Woman with Genital Herpes -- A Pregnant Woman with Genital Warts -- A Gay Man with Diarrhea -- A Gay Man with Jaundice -- A Pregnant Woman Who is a Contact of a Man with Infectious Syphilis -- An HIV-Infected Man with Anal Pain, Anal Discharge, and Bleeding -- A Young Girl with Anogenital Lumps.
Keywords: Medicine; Dermatology; Family medicine; Gynecology; Urology; Medicine & Public Health; Urology/Andrology.; Gynecology; Dermatology; General Practice / Family Medicine